Analysis of Sharia Compliance on Fintech Lending Platforms: A Quantitative Study on User Perceptions - Syarif Hidayatullah (LP2M IAIN Palopo, 2026)
The rapid growth of Islamic fintech lending in Indonesia has raised concerns about the actual level of sharia compliance perceived by its users. This study aims to analyze the influence of sharia compliance, transparency, and trust on user perceptions of Islamic fintech lending platforms. A quantitative approach was employed using a survey of 200 users of Islamic fintech lending in Indonesia, selected through purposive sampling. Data were collected via a structured questionnaire using a 5-point Likert scale and analyzed using SPSS version 26 through validity tests, reliability tests, classical assumption tests, and multiple linear regression. The results show that all instruments are valid (r-count > 0.138) and reliable (Cronbach's Alpha > 0.70). The classical assumption tests confirm that the data are normally distributed, free from multicollinearity (VIF < 10), and free from heteroscedasticity. The multiple regression analysis reveals that sharia compliance (β = 0.412; t = 6.842; p < 0.001), transparency (β = 0.276; t = 4.521; p < 0.001), and trust (β = 0.198; t = 3.314; p = 0.001) significantly influence user perceptions. The simultaneous F-test indicates F = 143.567 with p < 0.001, while the coefficient of determination (Adjusted R²) is 0.682, meaning that 68.2% of the variance in user perceptions can be explained by the three independent variables. The findings imply that sharia compliance is the dominant determinant of positive user perception, suggesting that Islamic fintech operators must strengthen DSN-MUI fatwa adherence, akad transparency, and ethical trust-building mechanisms to maintain user confidence.